2014
DOI: 10.36076/ppj.2014/17/494
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency of the Composite Nerve Supply to the Knee Joint as a New Technique for Relieving Osteoarthritic Pain: A Preliminary Report

Abstract: We report a new technique for pulsed radiofrequency (PRF) of the entire nerve supply of the knee as an option in treating osteoarthritis (OA) of knee. We targeted both sensory and motor nerves supplying all the structures around the knee: joint, muscles, and skin to address the entire nociception and stiffness leading to peripheral and central sensitization in osteoarthritis. Ten patients with pain, stiffness, and loss of function in both knees were treated with ultrasonography (USG) guided PRF of saphenous, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
0
21
0
2
Order By: Relevance
“…Two records were not published in English or Chinese. Finally, a total of 20 eligible articles were included in our meta-analysis [ 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two records were not published in English or Chinese. Finally, a total of 20 eligible articles were included in our meta-analysis [ 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Figure 2) It is formed by an infrapatellar branch from the SN, anterior division of obturator nerve, medial femoral cutaneous nerve, and NVM. It supplies the skin over the anteromedial aspect of the knee joint, retinaculum, collateral ligaments, and capsule of the knee joint [15].…”
Section: Adductor Canalmentioning
confidence: 99%
“…Erdem and Sir ( 12 ) investigated the effects of ultrasound-guided knee radiofrequency treatment on knee joint pain in patients with severe knee OA or patients who underwent knee arthroplasty and indicated that perceived pain and disability in the knee medial nerves were relieved after the treatment. Relevant studies have confirmed that pulsed radiofrequency treatment for the knee joint, a novel technique for relieving pain in OA, is able to reduce pain, relax the muscles and improve knee function ( 13 ). Such injuries stimulate large increases in the levels of catabolic species, which contribute to progressive cartilage destruction in the synovial fluid ( 14 ).…”
Section: Introductionmentioning
confidence: 99%